Session Rating of Perceived Exertion Is a Superior Method to Monitor Internal Training Loads of Functional Fitness Training Sessions Performed at Different Intensities When Compared to Training Impulse - Falk Neto, Joao Henrique; Tibana, Ramires Alsamir; de Sousa, Nuno Manuel Frade; Prestes, Jonato; Voltarelli, Fabricio Azevedo; Kennedy, Michael D. (Frontiers in Physiology, 2020)
Despite its increase in popularity, little is known about how to best quantify internal training loads from functional fitness training (FFT) sessions. The purpose of this study was to assess which method (training impulse – TRIMP or session-rating of perceived exertion – sRPE) is more accurate to monitor training loads in FFT. Eight trained males (age 28.1±6.0 years) performed an ALL-OUT FFT session and an intensity-controlled session (RPE of 6 out of 10). Internal load was determined via Edward’s TRIMP (eTRIMP), Bannister’s TRIMP (bTRIMP) and sRPE. Heart rate was measured continuously during the session, while blood lactate and rate of perceived exertion were measured at baseline, and immediately and 30 minutes after the sessions. ALL-OUT blood lactate and RPE were significantly higher immediately and 30 minutes after the session compared to the RPE6 condition. ALL-OUT training load was significantly different between conditions using bTRIMP (61.1 ± 10.6 vs 55.7 ± 12.4 au), and sRPE (91.7 ± 30.4 vs 42.6 ± 14.9 au), with sRPE being more sensitive to such differences (p = 0.045, ES = 0.76, and p = 0.002, ES = 1.82, respectively). No differences in the training loads of the different sessions were found using eTRIMP (93.1 ± 9.5 vs 84.9 ± 13.7 au, p = 0.085). Only sRPE showed a significant correlation with lactate 30-min post session (p = 0.015; ρ = 0.596, large). Conclusion: sRPE was more accurate than both TRIMP methods to represent the overall training load of the FFT sessions. While the use of sRPE is advised, further research is necessary to establish its ability to reflect changes in fitness, fatigue, and performance during a period of training.